COMPARATIVE STUDY OF THEORY MAQASID AL-SHARI'AH MEMORIAL AHMAD AL-RAYSUNI DAN JASSER AUDA - Amin, Muhammad Syamsul; Agustar, Armi (Fakultas Agama Islam UNISMA, 2023)
Ahmad al-Raysuni and Jasser Auda are two contemporary Muslim intellectuals who focus on exploring the theme of maqasid al-shari'ah. Even though they both pursue maqasid themes, both al-Raysuni and Auda represent their own different styles of thought. Al-Raysuni represents the traditional maqasid style of thought that was introduced and developed by previous scholars. Whereas Auda represents a modern maqasid style that carries the spirit of a contemporary era which is completely different from traditional views. Academically, the differences above indicate the existence of different methods in understanding and applying the theory of maqasid al-shari'ah. Therefore, researchers feel intrigued to explore and examine the extent to which the methods differ from the two. Departing from this anxiety, the researcher wishes to compare the views of Ahmad al-Rasysuni and Jasser Auda on maqasid al-Syari'ah. The type of this study is literature or literature review, the approach used is comparative; by mapping the thoughts of the two figures in terms of the determination method maqasid al-shari'ah. The object of the study is the thoughts of the two figures, and the research data is obtained from books written by both of them and related journals. From this study the authors found several things, namely: First both al-Raysuni and Auda both based their thoughts on classical sources of Islamic law regarding maqasid al-shari'ah. Second, al-Raysuni adheres to the study of classical maqasid and contextualizes it to the modern world with theoryfikr maqasidi andtaqrib-taglibnya, while Auda reconstructs the maqasid as an approach